Endless Revision Loop Syndrome: Fenomena Stres Berkepanjangan pada Mahasiswa Penyusun Tugas Akhir - Septi Gumiandari; Siti Fatimah Nur I'aly Hasanah (Ad-Dariyah: Jurnal Dialektika, Sosial dan Budaya, 2026)
The thesis completion process frequently traps students in repetitive and unpredictable revision cycles, triggering prolonged stress and impeding timely graduation. This study aims to: (1) explore students' subjective experiences in confronting repeated revisions; (2) identify the determinant factors causing this phenomenon; (3) understand the dynamics of chronic stress that develops; and (4) formulate a new psychological construct termed Endless Revision Loop Syndrome (ERLS). A qualitative phenomenological approach was employed, involving five university graduates recruited through purposive sampling and in-depth interviews. The findings reveal that all informants experienced feeling 'trapped' in repetitive draft revision cycles without a predictable endpoint, accompanied by frustration, stagnation, and a crisis of self-confidence stemming from inconsistent supervisory guidance. Determinant factors include supervisor inconsistency, institutional bureaucratic rigidity, limited access to primary references, and low student self-efficacy. Psychological stress progressed from mild cognitive load to chronic distress manifesting as psychosomatic health disorders, defensive procrastination, and social isolation. ERLS is constructed as a specific psychological distress condition triggered by the interaction between external barriers and internal vulnerability, forming a subjective belief that the thesis process has no clear termination point, yet can be disrupted through mental resilience, assertive communication, and social support. This study contributes theoretically by introducing a new nomenclature in academic stress discourse, with practical implications for institutions in designing more responsive and transparent supervisory systems